HEREDITY IN THE SYSTEM OF CHILD HEALTH FORMING FACTORS - Nadiіa Trush (Vasyl Stefanyk Precarpathian National University, 2018)
The article deals with the influence of heredity on the formation of human health. Every human being gets from nature everything to become a individual, but it becomes a full member of a society only when there are proper conditions for this. It is therefore important to identify as soon as possible the impacts of certain types of activities and create appropriate conditions for their development.It is thanks to heredity that conservation takes place over a long period of time, which reaches hundreds of millions of years. The variability unlike heredity provide for change and the appearance of new signs in people. The variability inherent in individuals, easily adapts to changes, provides survival in an ever-changing environment.Of course, each man is individual, and each genetically implies those or other factors that manifest throughout life. But everyone has the opportunity to be more or less healthy and happy. It is in childhood that the path of development for which a person will follow until the end of life is laid. Therefore, parents play a vital role in the health and development of their child. Key words: heredity, health, genetic information, genotype.